The Baptism of Jesus in Light of Jewish Ritual Practice - Grinṿald, Itamar (Neotestamentica, 2016)
A pivotal issue in the synoptic accounts of the baptism of Jesus concerns the presence or absence of John the Baptiser in the event. The Gospel of Mark makes clear that John was present, while the Gospel of Luke removes John from the scene, altogether. The Gospel of Matthew inclines to follow the Markan account, while the Gospel of John inclines to follow that of Luke. The question is: was John present and then removed from the story for theological reasons, or was he absent and then introduced into the scene for similar reasons? This article examines these issues in the context of ritual praxis and ritual theory and suggests that the account found in Luke follows the Jewish ritual of full immersion with no attending presence of a “baptiser.” The article examines the Jewish rites of full immersion done mainly for purifying purposes, and follows additional accounts of the activity of John the Baptist in connection with the baptism of Jesus.